MPM-DEM simulation of woody debris flow interaction with slit-check dams - Liu Ming; Xiaoqin Lei; Xinpo Li; Siming He; Xiaojun Guo; Liangliang Wang (Journal of Hydrology, 2026)

Contributions of sub-basins runoff to debris flow propagation at a basin scale: A numerical study in the Meilong Basin, China - Wei Liu; Zhen Tan; Jihao Jian; Siming He; Xuanmei Fan (Geomorphology, 2026)

Field investigation and numerical study of Bujueyida debris flow in Ganluo County (Sichuan, China) on 20 July 2024 - Jihao Jian; Wei Liu; Siming He; Zhen Tan (Landslides, 2026)

Mechanistic study on propoxate-induced neurotoxicity and addictive potential via blood-brain barrier disruption and GABAergic pathway activation - Renjuan Cao; Siming Ding; Jihong Cai; Jingxian Zhang; Xin Liu; Yuan Ren; Chao Liu (Toxicology, 2026)

Comprehensive Transcriptomic and Proteomic Profiling of CILD40 with Novel Compound Heterozygous Mutations of DNAH9 - Siming Kong; Mingshuo Wang; Xuedong Wang; Yakun Liu; Pengfei Wang; Wenyan Song; Ziye Chen; Yuxin Su; Canhong Xiang; Yunfang Wang; Hui Bai (Phenomics, 2026)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by impaired ciliary motility that leads to respiratory symptoms, laterality defects, and other systemic abnormalities. Despite significant advancements in genetic research identifying over 50 causative genes and enabling genetic diagnosis in approximately 90% of cases, comprehensive phenotypic characterization remains underexplored. We investigated two respiratory asymptomatic individuals (sisters) who exhibited laterality defects in a three-generation family, both of whom harbored novel compound heterozygous mutations (NM_001372.4:c.308del and NM_001372.4:c.11845G > A) in the dynein axonemal heavy chain 9 ( DNAH9 ) gene associated with primary ciliary dyskinesia-40 (CILD40). Structural modeling and western blotting analysis of HEK-293T cells demonstrated that the frameshift mutation abolished DNAH9 stability, whereas the missense mutation disrupted hydrogen bonds, leading to partial protein destabilization. Peripheral blood RNA sequencing revealed extensive dysregulation of axonemal and intraflagellar transport genes, implicating defects in microtubule-based motility in the two affected siblings with biallelic DNAH9 mutations, but not in their heterozygous family members or one unaffected relative. Plasma proteomic analysis of patients with CILD40 identified significant enrichment of pathways related to platelet activation, complement and coagulation cascades. Further comparative analysis with a patient with PCD caused by a CCDC40 mutation (CILD15 subtype) revealed differential signatures in CILD40, highlighting the potential of plasma proteomics for understanding distinct pathogenic mechanisms across PCD subtypes. These findings underscore the critical role of DNAH9 compound heterozygous mutations in CILD40 and provide new insights into the genetic, transcriptional, and proteomic phenotypic heterogeneity of PCD.

Plant-derived CTLA-4-targeting miR152 via lipid nanoparticles potentiates doxorubicin efficacy in breast cancer immunochemotherapy - Hanyi Ye; Wei Jin; Yifan Feng; Ze Wu; Shuhui Sun; Mengyao Cui; Shun Lv; Bing Jin; Chang Liu; Siming Wang; Ying Li; Zhengqi Dong (Science China Life Sciences, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Multi-level magma reservoir and open system processes of the Tianchi caldera, Changbaishan Volcanic Field, NE China - Siming Chen; Tong Hou; Ronghao Pan; Diao Luo; Guoming Liu; Roman Botcharnikov (Journal of Volcanology and Geothermal Research, 2026)

A numerical study of the transition process from rock-ice avalanche to debris flow - Wei Liu; Benhong Xiang; Jihao Jian; Siming He; Lanhai Li (Landslides, 2026)

Serotonin as a psychosocial biomarker in 3PM psychiatry: from the social brain to personalised intervention - Shengjian Ni; Lixuan Guan; Yuxin Jin; Linjing Liu; Siming Zhu; Wenyang Zhao; Vijayaraj Kumar Palanirajan (EPMA Journal, 2026)

3D MPM simulation of the coseismic Daguangbao landslide with a state-dependent frictional weakening model - Xiaoqin Lei; Lei Zhu; Siming He; Xinpo Li; Liu Ming; Yu Luo (Landslides, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Berberine inhibits ISG15 and pyroptosis to attenuate diabetic kidney disease inflammation and fibrosis - Lingzhi Huang; Qinqin Chen; Xiaoxiao Liu; Liuqing Wang; Xingyue Liao; Siming Yuan; Liqin Tang (Apoptosis, 2026)

Purifying or polluting? Tracing membrane-based microplastics release for long-term drinking water safety - Shunyao Yu; Siming Xie; Yaya Zhu; Wei Wang; Zhitong Liu; Xian Bao; Jun Ma (Water Research, 2026)

A machine learning hybrid model for heat transfer per meter prediction of energy pipe pile - Siming Dong; Chenglong Wang; Hanlong Liu; Abdelmalek Bouazza; Xuanming Ding; Gangqiang Kong (Geothermics, 2026)

Numerical study on the damage evaluation of a check dam under boulder-enriched debris flow impact - Wei Liu; Shuaixing Yan; Siming He; Dongpo Wang (Engineering Geology, 2026)

A THM-coupled MPM framework for modelling rock-ice avalanches - Xiaoqin Lei; Siming He; Changbing Qin; Jidong Zhao; Gordon G.D. Zhou; Liu Ming (Computers and Geotechnics, 2025)

Cellulose-engineered janus periosteum with compartmentalized angiogenic and osteo-immunomodulatory abilities for bone regeneration - Wuyan Xu; Kun Liu; Jiaqing Chen; Junliang Liu; Siming Li; Hua Wang; Binghong Luo; Qingqi Meng (Carbohydrate Polymers, 2025)

Corrigendum to “Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region”. [Catena 260 (2025) 109423] - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

A thermal-pore-chemical-mechanics model for large landslides in the unsaturated case - Huanhuan Zhang; Wei Liu; Siming He; Xiong Tang; Wei Hu (Bulletin of Engineering Geology and the Environment, 2025)

A hierarchical conflict resolution strategy for collision avoidance in multi-ship encounter scenarios - Ni Shengke; Xian Guoliang; Zhao Zhijie; Wang Xinjian; Liu Guangqiang; Fan Yaxin; Fang Siming (Ocean Engineering, 2025)

Facile upcycling of color-mixed polyethylene terephthalate-based textile waste via mild solvolysis with a natural aromatic solvent - Yue Zhu; Jindan Tang; Siming Zhu; Yu Liu; Liping Lou; Qingqing Mei (Chemical Engineering Journal, 2025)

Complexes of Dendrobium officinale anthocyanins and polysaccharides: Structural characteristics, stability, antioxidant properties, and bioavailability - Bowen Sui; Yanling Sun; Jingzhi Wang; Yuan Cui; Haibo Xu; Daqing Zhao; Meichen Liu; Zhengqi Dong; Siming Wang; Shichao Liu (Food Bioscience, 2025)

Bioinspired ECM-specific microenvironment scaffold: A multi-biomimetic strategy spatially guides osteochondral regeneration - Kun Liu; Wuyan Xu; Lin Li; Wendong Zhang; Wei Wen; Shan Ding; Mingxian Liu; Changren Zhou; Siming Li; Qingqi Meng; Binghong Luo (Chemical Engineering Journal, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

A refined method for the simulation of catchment rainfall–runoff based on satellite–precipitation downscaling - Jihao Jian; Siming He; Wei Liu; Shuang Liu; Liping Guo (Journal of Hydrology, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Isolation and identification of native microalgae from the Yellow River Delta: A dual-focus study on the tolerance assessment of microalgae and their growth enhancement on Sesbania cannabina under saline-alkali stress - Xiao Yu; Siming Li; Jiahao Liang; Shenkun Liu; Yinchu Wang; Jianchao Yang; Chenggang Ren; Chunli Ji; Hongli Cui; Song Qin (Algal Research, 2025)

Correction: Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2025)

Prediction of near-surface conditions following the 2023/24 sudden stratospheric warming by the S2S project models - Jian Rao; Xiaoqi Zhang; Qian Lu; Siming Liu (Atmospheric Research, 2025)

Review of Research Progress on the Influence of Groundwater Discharge on Seabed Stability - Zhentian Jia; Hongxian Shan; Hanlu Liu; Zhengrong Zhang; Long Jiang; Siming Wang; Yonggang Jia; Yongzheng Quan (Journal of Marine Science and Engineering, 2025)
Submarine groundwater discharge (SGD) refers to the flow of groundwater that enters seawater through the seabed surface at the edge of the coastal shelf. During this discharge process, seepage and initiation can easily trigger seabed instability, which significantly influences the breeding, occurrence, and evolution of marine geological events. The narrow distribution of land near the coastline and the substantial flux of groundwater discharge are closely associated with typical seabed geological events, such as submarine landslides and collapse pits, which are prevalent in the sea area. This paper analyzes the current research status of SGD both domestically and internationally, elucidates the interaction mechanisms between groundwater discharge and the seabed, and integrates existing studies on discharge-induced slope instability, collapse pit formation, and seabed erosion and resuspension. It summarizes and evaluates the existing research on the influence of seabed groundwater discharge on the evolution of seabed geological structures, identifies key scientific problems that urgently need to be addressed, and proposes future research directions that require further emphasis. Additionally, the paper conducts research on the mechanisms by which groundwater discharge affects seabed stability, providing valuable insights for the study of coastal zones in China. It also offers a scientific basis for enhancing the understanding of the generation mechanisms of marine geological events and improving the technological capabilities for their prevention and control.

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Non-local μ(I) rheology improves landslide deposition modeling in MLS-MPM simulations - Shuxi Zhao; Yang Liu; Gianvito Scaringi; Xinpo Li; Siming He; Gang He; Lei Zhu (Engineering Geology, 2025)

The impact of school activity space layout on children's physical activity levels during recess: An agent -based model computational approach - Jiameng Cui; Xue Meng; Siming Qi; Junwen Fan; Wenxuan Yu; Hongxing Liu; Xiang Wang; Yu Zhang (Building and Environment, 2025)

Analysis of sediment re-formation factors after ginseng beverage clarification based on XGBoost machine learning algorithm - Jiabao Feng; Yuan Cui; Chunyan Jiang; Xueyuan Bai; Daqing Zhao; Meichen Liu; Zhengqi Dong; Shiting Yu; Siming Wang (Food Chemistry, 2025)

Studies of the binding mechanism between liquid smoke from tea tree branches and proteins in dry-cured tenderloin using 4D-DIA proteomics, synergistic multispectral analysis, and molecular docking techniques - Yanpei Huang; Siming Ren; Yuanyuan Liu; Ying Zhou; Jing Wan; Linggao Liu; Qiujin Zhu (Food Chemistry, 2025)

Experimental Investigation of Seismic Signal Characteristics Arising from Basal Stress Fluctuations in Granular Flow - Xiao Yu; Zheng Chen; Siming He; Wei Liu; Dongpo Wang (Rock Mechanics and Rock Engineering, 2025)

Reproduction of the chain process of debris flow blocking river at a catchment scale: a numerical study - Wei Liu; Chaojun Ouyang; Yao Tang; Siming He (Bulletin of Engineering Geology and the Environment, 2024)

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Regeneration of CO2 from CO2-rich absorbents using hollow fiber membrane contactors in liquid–liquid extraction mode - Siming Chen; Chunjin Zhang; Jingchao Liu (Chemical Engineering Journal, 2024)

CO prodrugs: a new scaffold of adamantane-fused norbornen-7-ones with tunable water solubility - Ce Yang; Xingyue Ji; G. S. Sainaga Jyothi Vaskuri; Xiaoxiao Yang; Wen Lu; Zhengnan Yuan; Dongning Liu; Siming Wang; Chalet Tan; Binghe Wang (Medicinal Chemistry Research, 2024)

Mesoporous carbon hollow spheres based sensitive SPME probes for in vivo sampling analysis of selected plant hormones in Chinese aloes - Yan Liu; Jiajia Han; Guosheng Chen; Siming Huang; Shuyao Huang; Juan Zheng; Jianqiao Xu; Fang Zhu; Gangfeng Ouyang (Analytica Chimica Acta, 2024)

A Thermo-Poro-Mechanics Model Predicts the Transition from Creep to Rapid Movement of Large Landslides - Huanhuan Zhang; Wei Liu; Siming He; Wei Hu (Rock Mechanics and Rock Engineering, 2024)

Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2024)

Experimental study on human evacuation onboard passenger ships considering heeling angle and opposite directions - Siming Fang; Zhengjiang Liu; Xinjian Wang; Ben Matellini; Jin Wang; Zaili Yang; Xinyu Zhang; Bo Wan; Shengke Ni (Ocean Engineering, 2024)

A numerical approach to the simulation of landslide motion by considering rock disintegration - Wei Liu; Lei Zhu; Siming He (Computers and Geotechnics, 2024)

A simplified single-phase depth-averaged model for rock-ice avalanche movement considering ice melting - Wei Liu; Siming He (Engineering Geology, 2024)

Influence of runoff on debris flow propagation at a catchment scale: a case study - Wei Liu; Siming He (Landslides, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Investigating the dynamic process of a rock avalanche through an MLS-MPM simulation incorporated with a nonlocal μ(I) rheology model - Shuxi Zhao; Siming He; Xinpo Li; Gianvito Scaringi; Yang Liu; Yu Deng (Landslides, 2024)

Time-varying impacts of green credit on carbon productivity in China: New evidence from a non-parametric panel data model - Peng Hou; Shuang Luo; Siming Liu; Yong Tan; David Roubaud (Journal of Environmental Management, 2024)

Unveiling the inverse antimicrobial impact of a hetero-chitooligosaccharide on Candida tropicalis growth and biofilm formation - Yangyang Liu; Ruilian Li; Yuchen Zhang; Siming Jiao; Tong Xu; Yuhang Zhou; Yujing Wang; Jinhua Wei; Wei Du; Morihisa Fujita; Yuguang Du; Zhuo A. Wang (Carbohydrate Polymers, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

The influence of biochar from animal and plant on the transformation of phosphorus during paper mill sludge composting - Siming Zhong; Zhen Yu; Xiaoming Liu; Meihua Zhao; Hongwei Rong (Environmental Science and Pollution Research, 2024)

Protective effect of retaining wall on rock avalanche: A case study of Nayong rock avalanche in China - Zhongfu Wang; Fengge Shi; Siming He; Xusheng Zhang; Jingying Wang; Enlong Liu (Journal of Mountain Science, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

An integrated model for simulating melt-driven debris flow in a snow-dominated catchment - Wei Liu; Siming He (Landslides, 2024)

Effect of hydrophobic sucrose esters with different fat acid composition and esterification degree on whipped cream properties - Di Zeng; Yongjian Cai; Tongxun Liu; Lihua Huang; Junwei Wang; Mouming Zhao; Siming Zhu; Qiangzhong Zhao (Food Hydrocolloids, 2024)

Effect of vegetation growth on morphological traits of vegetation and biomechanical features of roots - Yi Zhang; Wei Liu; Siming He (Plant and Soil, 2024)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Genome-resolved metagenomic insight into vanadate and ammonium elimination in sulfur-based autotrophic biosystem - Wenyue Yan; Siming Chen; Min Li; Sitong Liu; Baogang Zhang (Chemical Engineering Journal, 2023)

3D-exosomes laden multifunctional hydrogel enhances diabetic wound healing via accelerated angiogenesis - Han Peng; Huichen Li; Xi Zhang; Jiezhang Tang; Yongping Liang; Lipeng Qiao; Yun Zhu; Mengmeng Hou; Siming Wei; Zhaoxiang Zhang; Chaohua Liu; Xinmao Li; et al. (Chemical Engineering Journal, 2023)

Creep-to-Runout Transition of Large Landslides Controlled by Frictional Velocity Strengthening and Weakening (Vajont 1963, Italy) - Huanhuan Zhang; Siming He; Wei Liu; Yu Deng; Wei Hu (Rock Mechanics and Rock Engineering, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Review on the development of marine floating photovoltaic systems - Wei Shi; Chaojun Yan; Zhengru Ren; Zhiming Yuan; Yingyi Liu; Siming Zheng; Xin Li; Xu Han (Ocean Engineering, 2023)

A quantitative study of the factors influencing human evacuation from ships - Siming Fang; Zhengjiang Liu; Xihan Yang; Xinjian Wang; Jin Wang; Zaili Yang (Ocean Engineering, 2023)

Research on the distribution of S species in the pressure oxidation leaching process of SrS solution - Siming Chen; Dongping Duan; Yanjiang Li; Yan Liu; E Zhou (Minerals Engineering, 2023)

Glutathione-Responsive Sulfur Dioxide-Releasing Dendronized Chitooligosaccharide Polymer for Effective Treatment of Multidrug-Resistant Bacterial Infection - Haitao Yu; Jiejiao Liu; Qianwen Lin; Jun Liu; Siming Yu; Pinghua Sun; Jing Lin (Chemical Engineering Journal, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Kif15 deficiency contributes to depression-like behavior in mice - Junpei Wang; Qifeng Tu; Siming Zhang; Xiaomei He; Chao Ma; Xiaowei Qian; Ronghua Wu; Xinyu Shi; Zhangyi Yang; Yan Liu; Zhangji Dong; Mei Liu (Metabolic Brain Disease, 2023)

Emissions of formaldehyde and nitrogen dioxide from liquefied petroleum gas combustion - Jin Ye; Siming Shi; Tao Yu; Cong Liu; Jingguang Li; Zhen Ding; Zhijiong Huang; Hua Qian (Process Safety and Environmental Protection, 2023)

Towards designing dysphagia foods: Recent advances in influencing factors and computer modeling for the swallowing of thickened fluids - Shuhan Liu; Dongling Qiao; Zihang Cheng; Fengwei Xie; Siming Zhao; Binjia Zhang (Trends in Food Science & Technology, 2023)

Mapping and validation of quantitative trait loci associated with dorsal aleurone thickness in rice (Oryza sativa) - Yiwen Xu; Siming Chen; Mingming Xue; Xingyu Chen; Zhibo Liu; Xuefeng Wei; Ji-Ping Gao; Chen Chen (Theoretical and Applied Genetics, 2023)

Understanding spatial-temporal travel demand of private and shared e-bikes as a feeder mode of metro stations - Siming Liu; Fan Zhang; Yanjie Ji; Xinwei Ma; Yong Liu; Shuo Li; Xizhen Zhou (Journal of Cleaner Production, 2023)

Substratum virtualization in three-dimensional landslide modeling with the material point method - Shuxi Zhao; Lei Zhu; Wei Liu; Xinpo Li; Siming He; Gianvito Scaringi; Xiong Tang; Yang Liu (Engineering Geology, 2023)

On the supraglacial rock avalanches: Thermo-hydro-mechanical analysis considering ice-water phase transition - Chuan He; Enlong Liu; Siming He; Jianhai Zhang; Haotian Wei (Geomorphology, 2023)

Review of explainable machine learning for anaerobic digestion - Rohit Gupta; Le Zhang; Jiayi Hou; Zhikai Zhang; Hongtao Liu; Siming You; Yong Sik Ok; Wangliang Li (Bioresource Technology, 2023)

Application of artificial step-pools in natural hazard mitigation - Kehan Huang; Wei Liu; Mengzhen Xu; Siming He; Yifei Cui; Zhaoyin Wang (CATENA, 2023)

Innovation and green total factor productivity in China: a linear and nonlinear investigation - Siming Liu; Peng Hou; Yingkun Gao; Yong Tan (Environmental Science and Pollution Research, 2022)

Geological structure and failure mechanism of an excavation-induced rockslide on the Tibetan Plateau, China - Lei Zhu; Siming He; Jihao Jian; Jun Zhou; Bin Liu (Bulletin of Engineering Geology and the Environment, 2021)

Northern Hemisphere Sudden Stratospheric Warming and Its Downward Impact in Four Chinese CMIP6 Models - Jian Rao; Siming Liu; Yuanhao Chen (Advances in Atmospheric Sciences, 2021)

Modeling the landslide-generated debris flow from formation to propagation and run-out by considering the effect of vegetation - Wei Liu; Zongji Yang; Siming He (Landslides, 2021)

Citywide Traffic Analysis Based on the Combination of Visual and Analytic Approaches - Feng Liu; Gennady Andrienko; Natalia Andrienko; Siming Chen; Davy Janssens; Geert Wets; Yannis Theodoridis (Journal of Geovisualization and Spatial Analysis, 2020)

Correction to: Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Comprehensive modelling of runoff-generated debris flow from formation to propagation in a catchment - Wei Liu; Siming He (Landslides, 2020)

Simulating the process of the Jinshajiang landslide-caused disaster chain in October 2018 - Wei Liu; Nengpan Ju; Zhen Zhang; Zheng Chen; Siming He (Bulletin of Engineering Geology and the Environment, 2020)

Failure mechanism and dynamic processes of rock avalanche occurrence in Chengkun railway, China, on August 14, 2019 - Lei Zhu; Heng Liang; Siming He; Wei Liu; Qingyun Zhang; Gang Li (Landslides, 2020)

Dynamic simulation of rockslide-debris flow based on an elastic–plastic framework using the SPH method - Heng Liang; Siming He; Wei Liu (Bulletin of Engineering Geology and the Environment, 2020)

Dynamic process of the massive Xinmo landslide, Sichuan (China), from joint seismic signal and morphodynamic analysis - Xiuqiang Bai; Jihao Jian; Siming He; Wei Liu (Bulletin of Engineering Geology and the Environment, 2019)

Impact protection of bridge piers against rockfall - Siming He; Shuaixing Yan; Yu Deng; Wei Liu (Bulletin of Engineering Geology and the Environment, 2019)

Source characteristics and dynamics of the October 2018 Baige landslide revealed by broadband seismograms - Zhen Zhang; Siming He; Wei Liu; Heng Liang; Shuaixing Yan; Yu Deng; Xiuqiang Bai; Zheng Chen (Landslides, 2019)

Dynamic process simulation of construction solid waste (CSW) landfill landslide based on SPH considering dilatancy effects - Heng Liang; Siming He; Xiaoqin Lei; Yuzhang Bi; Wei Liu; Chaojun Ouyang (Bulletin of Engineering Geology and the Environment, 2019)

Measuring and estimating the impact pressure of debris flows on bridge piers based on large-scale laboratory experiments - Dongpo Wang; Zheng Chen; Siming He; Yang Liu; Hao Tang (Landslides, 2018)

Dynamic process simulation of rainfall-induced Sanxicun landslide based on a thermo-poro-elastic approach - Yu Luo; Wei Liu; Siming He; Jiang Yuanjun; Xiaoqing Lei (Natural Hazards, 2018)

Emission controls of mercury and other trace elements during coal combustion in China: a review - Yongchun Zhao; Jianping Yang; Siming Ma; Shibo Zhang; Huan Liu; Bengen Gong; Junying Zhang; Chuguang Zheng (International Geology Review, 2018)

Dynamic simulation of a mountain disaster chain: landslides, barrier lakes, and outburst floods - Wei Liu; Siming He (Natural Hazards, 2018)

Two-dimensional landslide dynamic simulation based on a velocity-weakening friction law - Wei Liu; Siming He; Xinpo Li; Qiang Xu (Landslides, 2016)

A two-layer model for simulating landslide dam over mobile river beds - Wei Liu; Siming He (Landslides, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

Characterization of fly ash from a circulating fluidized bed incinerator of municipal solid waste - Lin Zhang; Xiaowen Su; Zhixuan Zhang; Siming Liu; Yuxin Xiao; Mingming Sun; Jixin Su (Environmental Science and Pollution Research, 2014)

Effects of Frequency on the Dynamic Properties of Intact Rock Samples Subjected to Cyclic Loading under Confining Pressure Conditions - Enlong Liu; Runqiu Huang; Siming He (Rock Mechanics and Rock Engineering, 2012)

Dynamic Properties of Intact Rock Samples Subjected to Cyclic Loading under Confining Pressure Conditions - EnLong Liu; Siming He; Xinhua Xue; Jin Xu (Rock Mechanics and Rock Engineering, 2011)

Erratum to: Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)